Conditional survival of metastatic clear cell renal cell carcinoma: How prognosis evolves after cytoreductive surgery of primary tumor. (12th September 2021) - Shen, Haixiang; Liu, Jin; Liu, Wei; Sun, Jiazhu; Zheng, Xiangyi; Teng, Lisong; Wang, Xiao; Xie, Liping
Abstract: Introduction: Cytoreductive surgery is one of the recommended treatments for metastatic renal cell carcinoma, while the prognostic information of these patients treated with cytoreductive surgery is limited. In this study, we aimed to investigate the survival profiles based on conditional survival (CS) estimates in metastatic clear cell renal cell carcinoma (mccRCC) patients treated with cytoreductive surgery of primary tumor. Methods and materials: We identified and extracted mccRCC patients from the Surveillance, Epidemiology, and End Results database. We used Kaplan–Meier method to perform CS analyses. A multivariate Cox regression model was applied to explore the changes of well‐known prognostic factors. Results: Conditional overall survival (COS) and conditional cancer‐specific survival (CCSS) improved increasingly at all periods of survivorships compared to survival estimates at baseline in overall population of mccRCC. The 36‐month COS improved by 3.3%–6.4% given per 12 additional months of survivorships and the CCSS improved significantly from 45.1% (95% CI 42.8–47.3) at 12 months to 67.1% (95% CI 62.0–71.7) at 60 months. Much more survival gain was observed in patients with advanced disease. Furthermore, the prognostic significance of age and pathological factors diminished and even disappeared in a long‐term survivorship. Conclusions: Conditional overall survival and CCSS improved with time dynamically in mccRCC patients treated with cytoreductive surgery of primary tumor. Patients with advanced disease achieved significant survival gain and even could harvest a better prognosis given that the time of survivorship exceeds a certain period. Our findings could provide valuable and practical data for patient counseling and surveillance strategy making. Abstract : In this study, we investigated the survival profiles based on conditional survival estimates in metastatic clear cell renal cell carcinoma (mccRCC) patients treated with cytoreductive surgery of primary tumor. We found that COS and CCSS improved with time dynamically in all mccRCC patients treated with cytoreductive surgery of primary tumor.